Disease activity patterns over time in patients with SLE: analysis of the Hopkins Lupus Cohort - Györi, Noémi (Lupus Sci Med, 2017)
OBJECTIVE: To describe SLE disease activity patterns in the Hopkins Lupus Cohort. METHODS: Disease activity was studied in 1886 patients followed-up for 1–28 years. Disease activity patterns were defined using (1) Physician Global Assessment (PGA) and (2) modified SLE Disease Activity Index (M-SLEDAI) as follows: long quiescent (LQ), M-SLEDAI=0/PGA=0 at all visits; relapsing-remitting (RR), periods of activity (M-SLEDAI>0/PGA>0) interspersed with inactivity (M-SLEDAI=0/PGA=0); chronic active (CA), M-SLEDAI>0/PGA>0 at all visits. The pattern of first 3 consecutive follow-up years was determined in 916 patients as: persistent LQ (pLQ), persistent RR (pRR) and persistent CA (pCA), LQ, RR and CA pattern in each of the 3 years, respectively; mixed, at least two different pattern types were identified. RESULTS: The RR pattern accounted for the greatest proportion of follow-up time both by M-SLEDAI and PGA, representing 53.8% and 49.9% of total patient-years, respectively. The second most frequent pattern was LQ based on M-SLEDAI (30.7%) and CA based on PGA (40.4%). For the first 3-year intervals, the mixed pattern type was the most common (56.6%). The pRR was the second most frequent (M-SLEDAI 33.3%, PGA 26.5%), while pLQ (M-SLEDAI 6.4%, PGA 0.7%) and pCA were less frequent (M-SLEDAI 3.7%, PGA 16.3%). CONCLUSIONS: The RR pattern was the most prevalent pattern. LQ was achieved in a subset of patients, using the M-SLEDAI. However, the PGA captured mild activity missed on the M-SLEDAI in these patients. Over a 3-year perspective, less than half of patients maintained their original pattern.